2014
DOI: 10.7717/peerj.629
|View full text |Cite
|
Sign up to set email alerts
|

Stable hydrogen isotopes record the summering grounds of eastern red bats (Lasiurus borealis)

Abstract: Bats face numerous threats associated with global environmental change, including the rapid expansion of wind-energy facilities, emerging infectious disease, and habitat loss. An understanding of the movement and migration patterns of these highly dispersive animals would help reveal how spatially localized the impacts from these threats are likely to be on bat populations, thus aiding in their conservation. Stable hydrogen isotope ratios (δ2H) can be used to infer regions where bats have foraged during the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…, , Pylant et al. ), the specific months of precipitation that most strongly influence the food webs supporting them during the period of molt are unknown. Thus, we developed geostatistical models and maps of June–August δ 2 H‐precipitation (δ 2 H JJA ) values and mean annual δ 2 H‐precipitation (δ 2 H p ) values for North America using the online workspace IsoMAP (Bowen et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, , Pylant et al. ), the specific months of precipitation that most strongly influence the food webs supporting them during the period of molt are unknown. Thus, we developed geostatistical models and maps of June–August δ 2 H‐precipitation (δ 2 H JJA ) values and mean annual δ 2 H‐precipitation (δ 2 H p ) values for North America using the online workspace IsoMAP (Bowen et al.…”
Section: Methodsmentioning
confidence: 99%
“…, Pylant et al. ), which provides a solid basis for using δ 2 H hair values to identify potential summering regions of individuals of unknown geographic origin. If turbine‐killed bats are primarily from populations that summer around wind‐energy sites, then deceased individuals should have δ 2 H values characteristic of local precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…We chose deuterium for the isotopic analysis based on studies that focused on the correlation between δD k and δD p (Cryan et al , ; Fraser et al ; Ossa et al ; Plyant et al ). Plyant et al () found differences in the relationship of δD k and δD p in male and female red bats such that female red bats have a higher variance, which could be due to some females in the sample rearing young during that season and having different metabolic demands. Although a single equation could be used for both sexes, we decided that the R 2 of the combined equation (0.37) was not a large enough increase from the female's R 2 of 0.29 to choose it when the male's R 2 was 0.69 (Plyant et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Plyant et al () found differences in the relationship of δD k and δD p in male and female red bats such that female red bats have a higher variance, which could be due to some females in the sample rearing young during that season and having different metabolic demands. Although a single equation could be used for both sexes, we decided that the R 2 of the combined equation (0.37) was not a large enough increase from the female's R 2 of 0.29 to choose it when the male's R 2 was 0.69 (Plyant et al ). Therefore, we converted the eastern red bat hair isotope values (δD h ) using 2 equations: for males, normalδnormalDpgoodbreakinfix=(normalδnormalDh+13.95)/1.48 and for females, normalδnormalDp=(δDh+18.02)/1.75 (Plyant et al ; Data S1, available online in Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation